2021
DOI: 10.1186/s13023-021-02080-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel tortuosity as a prognostic marker for disease severity in Fabry disease

Abstract: Purpose The aim of this case control study was to evaluate the prognostic value of automatically quantified retinal vessel tortuosity from fundus images and vessel density from OCT-A in Fabry disease and to evaluate the correlation of these with systemic disease parameters. Methods Automatically quantified perimacular retinal vessel tortuosity (MONA REVA software), acquired by fundus imaging, and perifoveal retinal vessel density, acquired by optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…VT in patients with FD is speculated to be a result of intracytoplasmic storage of Gb3 within the endothelial cells, which can lead to endothelial proliferation and weakening of the vessel walls [1,13,32]. Hence, this could lead to a higher retinal VTI in these patients [46]. The finding of our study confirms data from previous studies where cohorts of patients with FD were analyzed to assess retinal VT with different methods [1,46].…”
Section: Discussionsupporting
confidence: 79%
“…VT in patients with FD is speculated to be a result of intracytoplasmic storage of Gb3 within the endothelial cells, which can lead to endothelial proliferation and weakening of the vessel walls [1,13,32]. Hence, this could lead to a higher retinal VTI in these patients [46]. The finding of our study confirms data from previous studies where cohorts of patients with FD were analyzed to assess retinal VT with different methods [1,46].…”
Section: Discussionsupporting
confidence: 79%
“…DNA damage-associated targets have already been investigated in human FD studies [33,34] reporting that lyso-Gb3, a deacylated form of Gb3, induces cellular stress, leading to FD human kidney cell DNA damage. FD patients also display neurovascular involvement such as cerebral stroke and microangiopathy [35][36][37]. Thus, we investigated different EC properties in control EC and EC derived from FD patients reporting either pain attacks (P1) or no pain (P2).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies Atiskova et al reported no difference in perifoveal vessel density when comparing FD patients with controls [ 23 ]. A study by Dogan et al reported a reduction of deep capillary vascular density in FD but no difference in superficial capillary vascular density in FD and controls [ 21 ].…”
Section: Discussionmentioning
confidence: 59%